Sea anemones (Cnidaria, Anthozoa, Actiniaria) in high sedimentation environments influenced by the Magdalena River (Colombian Caribbean) (2019)
Fifteen species of sea anemones (Cnidaria, Actiniaria) have been recorded so far in the Colombian Caribbean, comprising approximately 28% of the total number of known species in the Caribbean Sea. Most species recorded are associated with coral reef communities. However, in the region, no records of sea anemones are known from areas with high sedimentation conditions as is characteristic along the coastline of the Atlántico Department, in Colombia. In this area, organisms are exposed to a high degree of turbidity and sedimentation (~143.9x106 t year-1) as a result of their proximity to the Magdalena River mouth and the 26 micro-basins that flow along its coastline. Several observations and collections were made on soft bottoms, rocky, and artificial substrates in the sectors of Puerto Velero and Caño Dulce to determine the fauna that exist under these conditions. Four species of sea anemones were found belonging to the families Actiniidae and Aiptasiidae, and images from living specimens and cnidae are provided. Bunodosoma cavernatum and Exaiptasia diaphana are here recorded for the first time from the Colombian Caribbean. An updated list of sea anemones in the Colombian Caribbean, now comprising 34 taxa (i.e., 21 species and 13 identified at supra-specific levels), is provided.